Shooting the Pacific War : Marine Corps Combat Photography in WWII - Soule, Thayer (Book collections on Project MUSE., 2000)
"Shooting the Pacific War is based on Soule's detailed wartime journals. Soule was in the unique position to interact with men at all levels of the military, and he provides intriguing closeups of generals, admirals, sergeants, and privates - everyone he met and worked with along the way. Though he witnessed the horror of war firsthand, he also writes of the vitality and intense comradeship that he and his fellow Marines experienced."--Jacket.